2020
DOI: 10.1177/2192568220962439
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism Prophylaxis in Elective Spine Surgery

Abstract: Study Design: Review. Objective: Venothromboembolic (VTE) complications, composed of deep vein thrombosis and pulmonary embolism are commonly observed in the perioperative setting. There are approximately 500 000 postoperative VTE cases annually in the United States and orthopedic procedures contribute significantly to this incidence. Data on the use of VTE prophylaxis in elective spinal surgery is sparse. This review aims to provide an updated consensus within the literature defining the risk factors, diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 54 publications
(103 reference statements)
0
21
0
Order By: Relevance
“…vidence-based recommendations are lacking on the safe use of chemoprophylactic anticoagulation to prevent venous thromboembolic event (VTE) after spine surgery, as postoperative bleeding is a concern. [1][2][3] Moreover, some series have even found a paradoxically higher VTE incidence among patients receiving chemoprophylaxis. 2,4,5 A 2020 AO Spine survey found that 70.3% of surgeons base their decision to give chemoprophylaxis on individual patient risk rather than giving it routinely, most commonly based on comorbid disease burden.…”
mentioning
confidence: 99%
“…vidence-based recommendations are lacking on the safe use of chemoprophylactic anticoagulation to prevent venous thromboembolic event (VTE) after spine surgery, as postoperative bleeding is a concern. [1][2][3] Moreover, some series have even found a paradoxically higher VTE incidence among patients receiving chemoprophylaxis. 2,4,5 A 2020 AO Spine survey found that 70.3% of surgeons base their decision to give chemoprophylaxis on individual patient risk rather than giving it routinely, most commonly based on comorbid disease burden.…”
mentioning
confidence: 99%
“…This study protocol was considered feasible and safe. The risk of VTE in elective spinal surgery patients ranges from 0% to 31% [4]. Neither severe adverse events nor symptomatic VTE occurred in this study, and over 90% of the patients completed the protocol.…”
Section: Discussionmentioning
confidence: 67%
“…Ota et al studied the incidence of VTE and reported its remarkable increase in Japan from 1996 to 2011 [1]. In particular, orthopedic patients are at a higher risk of VTE among all patients, and those who undergo spinal surgery are at risk of VTE [2][3][4][5]. Moreover, patients who underwent spine fracture surgery have a higher VTE rate of 9.2% than that of other spine patients' VTE rate of 2.3%.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of venous thromboembolism (VTE), including pulmonary embolism and deep vein thrombosis (DVT) after spinal surgery ranges from 0.3% to 31% (Cheng et al 2010, Fineberg et al 2013, Glotzbecker et al 2009, Kim et al 2011a, Kim et al 2011b, Oda et al 2000; Solaru et al 2020, Takahashi et al 2012). The wide incidence range represents variability in patient population, presentation of symptoms, diagnostic methodology and post-acute care.…”
Section: Introductionmentioning
confidence: 99%